2012
DOI: 10.1112/blms/bds078
|View full text |Cite
|
Sign up to set email alerts
|

Boundary behaviour of functions which possess universal Taylor series

Abstract: It is known that, for any simply connected proper subdomain of the complex plane and any point in , there are holomorphic functions on that possess "universal" Taylor series expansions about ; that is, partial sums of the Taylor series approximate arbitrary polynomials on arbitrary compacta in Cn that have connected complement. This paper establishes a strong unboundedness property for such functions near every boundary point. The result is new even in the case of the disc, where it strengthens work of several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Another question concerns boundary behaviour, about which there is a growing literature [18], [9], [13], [14], [7], [16], [1], [5], [11]. For example, in the case of the unit disc D, it is known that if f ∈ U(D, 0), then f does not belong to the Nevanlinna class (see [15]) and there is a residual subset Z of the unit circle T such that the set {f (rζ) : 0 < r < 1} is unbounded for every ζ ∈ Z (see [4]).…”
Section: Introductionmentioning
confidence: 99%
“…Another question concerns boundary behaviour, about which there is a growing literature [18], [9], [13], [14], [7], [16], [1], [5], [11]. For example, in the case of the unit disc D, it is known that if f ∈ U(D, 0), then f does not belong to the Nevanlinna class (see [15]) and there is a residual subset Z of the unit circle T such that the set {f (rζ) : 0 < r < 1} is unbounded for every ζ ∈ Z (see [4]).…”
Section: Introductionmentioning
confidence: 99%
“…and z. Finally, we denote the characteristic function of a set A by A , and write v for the upper (respectively, b v for the lower) semicontinuous regularization of a function v. We begin by recalling two results, which can be found in [8] and [9], respectively. Theorem A.…”
Section: Preliminariesmentioning
confidence: 99%
“…Further, Müller, Vlachou and Yavrian [15] showed that the collection U( ; ) is independent of the centre of expansion , from which it follows that no function f in U( ; ) can be extended holomorphically beyond (see also Theorem 8.4 in Melas and Nestoridis [14]). Recently, this conclusion was substantially strengthened in [9], where it was shown that each such function f is unbounded near every 0 2010 Mathematics Subject Classi…cation 30K05, 30B30, 30E10, 31A05. Keywords: holomorphic functions; universal approximation; Taylor series; Laurent series; boundary behaviour; subharmonic functions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations